Sanggit dan Garap Lakon Banjaran Anoman Sajian Muh. Pamungkas Prasetyo Bayu Aji - Muhammad Alvian; Suwondo Suwondo (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2021)
This scientific thesis took the title of Sanggit and Garap in the Lakon Banjaran Anoman serving Muhammad Pamungkas Prasetyo Bayu Aji The problem revealed in this study is (1). What is the depiction of Anoman from various literature? (2). How does Sanggit and working on Lakon Banjaran Anoman serving Muhammad Pamungkas Prasetyo Bayu Aji? This research is qualitative research, data obtained through library studies, observations, and later interviews, validity. The step is to use Sugeng Nugroho’s exposure theory of sanggit discussion and work. The theory was used to examine the idea of work and implementation in Banjaran Anoman. The results obtained after conducting this study are descriptions of Anoman figures from various literatures both written and oral, sanggit analysis correlated with the text of the hypogram, the structure of the scene, the support, themes and mandates, as well as the work that is divided into: chess work, sabet work, work and embroidery that is found in banjaran anoman play. The clarification forms are (1) sanggit and catur work including janturan (janturan jejer and janturan adegan), pocapan (event pocapan and transitional pocapan), (2) sanggit and sabet work used are representative and thematic sabets used in the line scenes, (3) sanggit and gending include gending snares, gending scenes, and gending waran, and (4) sanggit and work on sulukan which includes pathetan , sendhon, and no-one.